A molecular perspective on lithium-ammonia solutions. - Zurek, E; Edwards, P; Hoffmann, R (2009)
A detailed molecular orbital (MO) analysis of the structure and electronic properties of the great variety of species in lithium-ammonia solutions is provided. In the odd-electron, doublet states we have considered: e-@(NH3)n (the solvated electron, likely to be a dynamic ensemble of molecules), the Li(NH3)4 monomer, and the [Li(NH3)4+.e-@(NH3)n] ion-pairs, the Li 2s electron enters a diffuse orbital built up largely from the lowest unoccupied MOs of the ammonia molecules. The singly occupied MOs are bonding between the hydrogen atoms; we call this stabilizing interaction H-->H bonding. In e-@(NH3)n the odd electron is not located in the center of the cavities formed by the ammonia molecules. Possible species with two or more weakly interacting electrons also exhibit H-->H bonding. For these, we find that the singlet (S=0) states are slightly lower in energy than those with unpaired (S=1, 2...) spins. TD-DFT calculations on various ion-pairs show that the three most intense electronic excitations arise from the transition between the SOMO (of s pseudosymmetry) into the lowest lying p-like levels. The optical absorption spectra are relatively metal-independent, and account for the absorption tail which extends into the visible. This is the source of Sir Humphry Davy's "fine blue colour" first observed just over 200 years ago.